THE ROLE OF BARIATRIC SURGERY IN NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD) MANAGEMENT: A PROSPECTIVE STUDY AT AFRIDI MEDICAL COMPLEX, PESHAWAR - Ahmad, Mushtaq; Alamgir, Maria; Ahmad, Waqar; Sahibzada, Abdul Haseeb (Journal of Ayub Medical College Abbottabad, 2026)
Abstract: Background: The prevalence of non-alcoholic fatty liver disease (NAFLD) has significantly increased due to the obesity pandemic.Reducing body weight by 5 to 10% in obese patients can improve all aspects of NAFLD. This study aimed to determine the Role of Bariatric Surgery in Non-Alcoholic Fatty Liver Disease (NAFLD). Methods: Over the course of one year, this prospective study was carried out from August 2021-august 2022.Patients undergoing laparoscopic sleeve gastrectomy (LSG) with a diagnosis of non-alcoholic fatty liver disease (NAFLD) were included.Preoperative data including demoraphics and Laboratory tests included HbA1c, lipid profile, fasting glucose, and liver function tests (ALT, AST, and GGT). The BARD score, NAFLD fibrosis score and De Ritis ratio (AST/ALT), , and the AST to platelet ratio index (APRI) were among the serum marker scores that were evaluated post-surgery at different follow ups of 3, 6, and 12 and 18 months. Results:. A total of 461 (50%) of the 922 patients had non-alcoholic steatohepatitis (NASH). A total of 382 (83%) patients showed continued improvement in steatosis at eighteen months post-surgery while 51 (37%) patients with F2 fibrosis and 165 (60%) of those with F1 fibrosis demonstrated lower fibrosis stage at 1 year following surgery. Conclusion: The degree of fibrosis, hepatic inflammation, and steatosis in obese people is found to be decreased after bariatric surgery and is a safe and successful surgical procedure in the management of non-alcoholic fatty liver disease. Keywords: Bariatric Surgery, Management, Non-Alcoholic Fatty Liver Disease (NAFLD), Sleeve gastrectomy